POLA PEMBINAAN DISIPLIN SANTRI MADRASAH IBTIDAIYAH (MI) KELAS VI DI ASRAMA PERSAHABATAN MA’HAD AL-ZAYTUN TAHUN AJARAN 2018/2019 - Supriyanto Supriyanto; Henri Peranginangin (Bajang Institute, 2022)
This study aims to find out the pattern of discipline development for the sixth grade Madrasah Ibtidaiyah students in the Ma'had Al-Zaytun friendship dormitory for the 2019 academic year and find out what factors influence the Discipline Development Pattern for the sixth grade Madrasah Ibtidaiyah (MI) Santri at the Mahad Al Friendship Dormitory. -Zaytun Year 2019. This research method uses qualitative descriptive by using a naturalistic qualitative approach. The object of this research is the Mudabir Dormitory and the teachers assigned to the Ma'had Al-Zaytun Friendship Dormitory. The data sources of this research use primary data and secondary data. The collection procedure uses observation, interviews and documentation. The results of this study indicate that the pattern of discipline development for students of Madrasah Ibtidaiyah (MI) class VI at the Mahad Al-Zaytun Friendship Dormitory looks good. This can be seen when students carry out activities and activities every day, from getting up in the morning until before going back to sleep. All student activities are guided, protected, and monitored by Mudabbir directly and assisted by teachers and student caregivers. The factors that influence the development of santri are the shortage of room supervisors, lack of security for supporting dormitories, shortage of supporting employees as maintenance of facilities.